A facility for laboratory mice with a natural microbiome at Charité - Universitätsmedizin Berlin - Drude, Natascha Ingrid; Nagel-Riedasch, Stefan; Roßhart, Stephan Patrick; Diefenbach, Andreas; Jordan, Stefan (Lab animal, 2024)
Mice with a natural microbiome are a promising research model for basic and applied science because of their closer resemblance to the human superorganism compared to mice born and raised under stringent hygiene conditions. Consequently, biomedical therapies developed and tested in “Wildling mice” hold great potential for successful translation into clinical applications. Over the past four years, scientists, veterinarians and institutional officials at Charité - Universitätsmedizin Berlin, supported by the University Hospital Erlangen, have designed a facility for Wildling mice and developed a conceptual framework for safe and ethical preclinical research involving mice with a natural microbiome.